Pengaruh Persistensi Laba dan Risiko Sistematik Pada Earnings Response Coefficient Perusahaan di Bursa Efek Indonesia - Kusmirawati, Ni Putu Ari; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 34 No 10 (2024), 2025)
This research analyzes the effects of earnings persistence and systematic risk on Earnings Response Coefficient. This research uses companies listed in the Kompas 100 Index on the Indonesian Stock Exchange during the 2019-2021 periods. Sample selection was carried out using a purposive sampling method and obtained 48 firms with quarterly financial reports as the object of observation. Earnings Response Coefficient was estimated by regressing cummulative abnormal return on unexpected earnings. Cummulative abnormal return was measured using market-adjusted model with 7 days event window around the event date. Data was analyzed by multiple linear regression. The results show that earnings persistence has no effect on Earnings Response Coefficient, while the systematic risk has a positive effect on Earnings Response Coefficient.